Single-cell sequencing reveals heterogeneity between pancreatic adenosquamous carcinoma and pancreatic ductal adenocarcinoma with prognostic value - Zhang, Deyu; Wu, Suna; Pan, Shubo; Wang, Meiqi; Wang, Zhen; He, Zixuan; Zhang, Guanghao; Cui, Fang; Song, Yihang; Li, Wanshun; Shi, Xiaohua; Huang, Haojie; et al. (Frontiers in Immunology, 2022)
Pancreatic adenosquamous carcinoma (ASPC) is a rare subtype of pancreatic cancer with lethal malignancy, and few studies have focused on the heterogeneity of ASPC. Here, we performed a single-cell sequencing procedure on pancreatic tumour tissue from an ASPC patient and a patient with high-grade IPMN. Through combined analysis of single-cell sequencing data from 5 PDAC patients, 1 IPMN patient and 1 ASPC patient in a public database, we identified 11 main types of cells, including macrophages, B cells, cancer stem cells, ductal cells, fibroblasts, endo/stellate cells, neutrophils, acinar cells, T cells, NK cells, dendritic cells and mast cells. Then, the different characteristics and differentiation paths of the immune microenvironment among IPMN, ASPC and PDAC in macrophages, T cells and cancer-associated fibroblasts (CAFs) were identified through multiple bioinformatics analyses. Two novel special cancer-associated fibroblasts were identified as nonreactive CAFs and i&my CAFs. Then, cancer cells in duct cells were identified using infercnv software. Two ASPC-specific subgroups of cancer cells with squamous cell features were identified. Finally, the identified specific CAFs and cancer cells were mapped to the TCGA-PAAD cohort through cibersoftx software. All of these identified subgroups were calculated to have significant prognostic value in pancreatic cancer patients. These findings will promote the clinical application of single-cell sequencing data of pancreatic cancer and deepen our understanding of ASPC.